Long-wavelength GaInNAs/GaAs Vertical-cavity Surface-emitting Laser for Communication Applications - Chaqmaqchee, Faten A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2020)
This paper presents a comprehensive study of optical and electrical properties of vertical-cavity surface-emitting lasers(VCSELS) for long wavelength communication applications. The device consists of GaInNAs/GaAs multi-quantum wells QWs that enclosed between standard top and bottom epitaxially grown on AlGaAs/GaAs distributed Bragg reflectors. The impact of driven currents and injecting optical powers through QWs layers on the output light emission is addressed. Room temperature spectra measurements are performed at various applied currents using 980 nm pump laser and maximum intensity amplitude at around 21 dB was achieved.